2020
DOI: 10.2166/wst.2020.451
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of methylene blue onto betel nut husk-based activated carbon prepared by sodium hydroxide activation process

Abstract: In this study, activated carbon (AC) was prepared from agro-waste betel nut husks (BNH) through the chemical activation method. Different characterization techniques described the physicochemical nature of betel nut husks activated carbon (BNH-AC) through FTIR, BET, SEM, and pH point of zero charge. Later, the produced AC was used for methylene blue (MB) adsorption via numerous batch experimental parameters: initial concentrations of MB dye (25–250 mg/L), contact time (0.5–24 hours) and initial pH (2–12). Dye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…A result of this is that the end product may well be reused effectively if areca nutshell waste is turned into nanoparticles. 14 Chemical synthesis of reduced graphene oxide (RGO) involves hazardous chemicals. To eliminate this drawback, biobased extracts are used in the synthesis process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A result of this is that the end product may well be reused effectively if areca nutshell waste is turned into nanoparticles. 14 Chemical synthesis of reduced graphene oxide (RGO) involves hazardous chemicals. To eliminate this drawback, biobased extracts are used in the synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…A result of this is that the end product may well be reused effectively if areca nutshell waste is turned into nanoparticles. 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, prospective raw materials will normally get treated physically or chemically or by combination of both methods to produce porous network on their surface. In general, carbon-based materials and their derivatives can be processed into materials with desired porosity for different applications (Rashid et al 2018;Bardhan et al 2020). Some notable carbon materials are diamond, graphite, coke, fullerenes, carbynes and their derivatives such as carbon nanotube, graphene, carbon black and activated carbon (AC) whereby AC gains the most attention within the carbon derivatives group as indicated by its high production and usage frequency every year (Malek & Laiman 2018;Rashid et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is the edible fruit of the Areca palm tree and is native to South-East Asia and the Pacific islands. Investigations have shown that fragments of the Areca fruit such as betel nut husk [39,40], Areca nutshell [41], and Areca nut pod [42] had been used for the preparation of AC for dye removal.…”
Section: Introductionmentioning
confidence: 99%